Memahami Konsep Belajar Anak Usia Dasar: Studi Analisis Teori Belajar Carl Rogers Serta Penerapannya di Sekolah Dasar - Hidayat, Wahyu; Sedya Santosa (Journal of Primary Education Research, 2024)
The importance of understanding Carl Rogers' learning theory and its application to elementary age children not only has an impact on improving the quality of the learning process, but can also support the holistic development of children's individual potential. This research is qualitative research with a literature review approach. This research includes a comprehensive review of the literature relevant to Carl Rogers' learning theory and its application in the context of primary childhood learning. Analyze the literature to identify key concepts in Carl Rogers' theory of learning. This may include concepts such as self-concept, self-actualization, unconditional appreciation, and empathy as the main focus. Review the literature that discusses the application of Carl Rogers' learning theory in elementary age learning. It involves reviewing research results, case studies, and practical implementation of Rogers' concepts in classrooms or primary age educational environments. The results of this study are explained pointedly from the urgency of Carl Rogers learning theory for children, the concepts underlying Carl Rogers learning theory, the implementation of the basic concepts of Carl Rogers learning theory in elementary age education, and analysis of the application of Carl Rogers learning theory in elementary school age children.. The implications through this study are expected to find strategies and approaches that can make a positive contribution to elementary age learning, in accordance with the learning principles advocated by Carl Rogers.